Mapping the journey of transition: a single-center study of 170 childhood-onset GH deficiency patients. Issue 8 (13th August 2021) - Doknic, Mirjana; Stojanovic, Marko; Soldatovic, Ivan; Milenkovic, Tatjana; Zdravkovic, Vera; Jesic, Maja; Todorovic, Sladjana; Mitrovic, Katarina; Vukovic, Rade; Miljic, Dragana; Savic, Dragan; Milicevic, Mihajlo; et al.
Abstract : Objective: To analyze metabolic parameters, body composition (BC), and bone mineral density (BMD) in childhood-onset GH deficiency (COGHD) patients during the transition period (TP). Design: Single- center, retrospective study was performed on 170 consecutive COGHD patients (age 19.2 ± 2.0 years, range 16–25) transferred after growth completion from two pediatric clinics to the adult endocrine unit. Two separate analyses were performed: (i) cross-sectional analysis of hormonal status, metabolic parameters, BC, and BMD at first evaluation after transfer from pediatrics to the adult department; (ii) longitudinal analysis of BC and BMD dynamics after 3 years of GH replacement therapy (rhGH) in TP. Results: COGHD was of a congenital cause (CONG) in 50.6% subjects, tumor-related (TUMC) in 23.5%, and idiopathic (IDOP) in 25.9%. TUMC patients had increased insulin and lipids levels ( P < 0.01) and lower Z score at L-spine ( P < 0.05) compared to CONG and IDOP groups. Patients treated with rhGH in childhood demonstrated lower fat mass and increased BMD compared to the rhGH-untreated group ( P < 0.01). Three years of rhGH after growth completion resulted in a significant increase in lean body mass (12.1%) and BMD at L-spine (6.9%), parallel with a decrease in FM (5.2%). Conclusion: The effect of rhGH in childhood is invaluable for metabolic status, BC, and BMD in transition to adulthood. Tumor-related COGHD subjects are at higher risk for metabolic abnormalities, alteration of body composition, and decreased BMD, compared to those with COGHD of other causes. Continuation of rhGH in transition is important for improving BC and BMD in patients with persistent COGHD.